2019
DOI: 10.1590/s0100-83582019370100102
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Imazamox with Centrifugal Energy Spray Nozzle on Eichhornia crassipes and Economic Analysis of Control Viability

Abstract: The efficacy of imazamox to control Eichhornia crassipes with a centrifugal energy spray nozzle at doses and volumes of spray solution and the costs of mechanical and chemical control of aquatic plants were evaluated in this study. Imazamox doses consisted of 200, 400, and 600 g a.i. ha-1, and spray solution volumes consisted of 25, 50, and 100 L ha-1, with a control (without herbicide application) and ten replications. Applications were performed with a centrifugal energy spray nozzle. The evaluations were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…A total number of sixteen empirical studies collectively aimed at uncovering the cost-benefit analysis of deploying various control and utilisation methods in dealing with water hyacinth were compared. The biological method of control is the most commonly used [5,54,55] while the chemical [5,56], integrated [5,57], and mechanical [56] are other controlling methods used. These studies used different models for their analysis, and the choice of these models was based majorly on assumptions such as prevailing market prices, opportunity costs of fishermen, farmers, and traders' lost revenues [55], prevented volume of water that would have been lost due to evapotranspiration [5,51,54], potential revenue in tourism and real estate markets [5,57].…”
Section: Techno-economic Analysis Of Water Hyacinth Mitigationmentioning
confidence: 99%
See 1 more Smart Citation
“…A total number of sixteen empirical studies collectively aimed at uncovering the cost-benefit analysis of deploying various control and utilisation methods in dealing with water hyacinth were compared. The biological method of control is the most commonly used [5,54,55] while the chemical [5,56], integrated [5,57], and mechanical [56] are other controlling methods used. These studies used different models for their analysis, and the choice of these models was based majorly on assumptions such as prevailing market prices, opportunity costs of fishermen, farmers, and traders' lost revenues [55], prevented volume of water that would have been lost due to evapotranspiration [5,51,54], potential revenue in tourism and real estate markets [5,57].…”
Section: Techno-economic Analysis Of Water Hyacinth Mitigationmentioning
confidence: 99%
“…Cost-benefit analysis (CBA) and producer price index (PPI) were the most common appraisal methods, as seen in Table 3. Arp et al [51] adopted the Residual Value Method, while the authors of [56] did not adopt any known project appraisal methods. Although the studies unanimously concluded that the benefits of control methods outweighed their costs, reliability of the premised assumptions, neglect of time, value of money, and quantification of extrinsic benefits are major shortcomings of assessing economic visibility of the control method.…”
Section: Techno-economic Analysis Of Water Hyacinth Mitigationmentioning
confidence: 99%
“…In addition, sulfentrazone, imazapyr, imazapic, metsulfuron-methyl and sulfosate are very efficient to control water hyacinth (Neves et al 2002). Imazamox is also an effective herbicide to control water hyacinth (Emerine et al 2010;Gettys et al 2014;Garlich et al 2019). New herbicides are required to be used.…”
Section: Chemical Controlmentioning
confidence: 99%
“…Os custos estimados de espécies invasoras em todo o mundo totalizaram mais de US $ 1,4 trilhão (5% da economia global) e somente nos EUA, os prejuízos econômicos estimados (bem-estar e perdas de produção) e os custos de controle associados às espécies invasoras foram de aproximadamente US$ 120 bilhões anuais (PIMENTEL;ZUNIGA;MORRISON, 2005). No Brasil esse custo chegou a superar 50 mil dólares ao mês em reservatório de 276 hectares (GARLICH et al, 2019) e 51 mil reais por hectare em um braço de reservatório com 22 hectares (SCHEER; LISBOA; BURDA, 2016).…”
Section: Introductionunclassified
“…algas marinhas entre 5 e 6 bilhões de dólares/ano) e uso ornamental (LEWIS; TRURSBY, 2018). Em contraste com os benefícios, o crescimento excessivo destas plantas endêmicas ou invasoras causam impacto negativo a saúde humana, irrigação, pesca, vida selvagem, recreação e navegação (GETTYS;PETTY,2014;GARLICH et al, 2019).…”
Section: Introductionunclassified